Application of real time tidal acquisition and processing system for hydrographic survey and dredging operations - Mahmud, Mohd. Razali; Othman, Rusli; Din, Usmuni (Faculty of Geoinformation Science and Engineering, 2008)

(untitled)
Tidal occurrence is an interesting phenomena and stores various knowledge in which requires continuous studies. Due to the position of Peninsular Malaysia that is surrounded by water, the studies on tide is important especially in determining tidal prediction, mean sea level and chart datum. These components can be determined through tidal analysis. The tidal data is obtained manually in non real time using typical tide gauge or digital tide gauge. The typical tide gauge will produce tidal data in analogue form while the digital tide gauge will produce tidal data in digital form. This data will be used to correct sounding values by post processing. Although some studies have claimed that on-line tidal corrections are possible to correct for sounding, unfortunately to–date these studies are not implemented widely in hydrographic surveying. On-line tidal corrections would enable sounding to be corrected immediately and hence will be significant for most hydrographic survey and dredging operations. Furthermore, to enable the on-line tidal corrections, the digital tide gauge will be integrated with radio link to enhance the realibility and validity of data. Hence, software known as UTM-Tidal Analysis and Prediction Software (µ-TAPS) that can process data automatically have been used in this research. The concept used by this software is based on the harmonic method using least squares estimation. In accessing the capabilities of µ-TAPS, the results of the computational analysis and tidal prediction were compared with the Tide Tables produced by the Royal Malaysian Navy (RMN) at Johor Bahru tidal observation stations using a minimum period of four month of data. In conclusion, the software developed can be an alternative for tidal analysis and prediction in Malaysia